MENGUKUR IMUNITAS PEJABAT PELAKSANA PERPPU COVID-19 DENGAN ASAS EQUALITY BEFORE THE LAW - Agung Barok Pratama (SUPREMASI HUKUM, 2021)
The immunity of officials implementing Perppu 1/2020 is in the public spotlight because it is not following “the principles of the rule of law and” injures the sense of justice in society because there are exceptions to legal “action. The principle of equality before the law” becomes a fundamental basis in viewing the position and position of every citizen. Therefore, it is necessary to measure the extent of impunity in the enforcement process for alleged violations of the law and its implications for the principle of Equality Before The Law. Based on the focus of the study, “the method used in this research is normative legal research and the statutory approach” is the basis for this writing. The paper concludes that Perppu 1/2020 does not necessarily provide absolute immunity to the implementing officials of the Perppu, but is limited (conditional) and the legal process is still carried out so as not to “violate the principles of the rule of law. Keywords : Immunity, Official, Perppu